FRI0477 Isolated Arthritis Revealing an Underlying Anti-Synthetase Syndrome: Results from a Multicentre International Study. (9th June 2015) - Cavagna, L.; Govoni, M.; Lopez Longo, F.J.; Airò, P.; Neri, R.; Sifuentes Giraldo, W.A.; Iannone, F.; Nuno, L.; Montecucco, C.; Caporali, R.; Furini, F.; Foschi, V.; et al.
Abstract : Background: Articular involvement is reported to occur in up to 85% of patients with antisynthetase syndrome (ASSD) and it may be the only onset feature, although with frequencies and characteristics not still defined Objectives: To determine in a large international cohort of anti Jo-1 positive ASSD the prevalence of isolated arthritis at disease onset. To describe the clinical, serological and radiological characteristics and evolution of these patients Methods: We included all anti Jo-1 positive patients referring to participating centres and with an isolated arthritis at disease onset. The pattern of articular involvement, radiological and serological characteristics of patients were analysed. IgM-Rheumatoid factor (RF) was assessed by immunonephelometry; anti-cyclic citrullinated peptide antibodies (ACPA) by commercial second-generation ELISA kits; anti Jo-1 and anti-Ro positivity by commercially available ELISA kits Results: An isolated arthritis was the first manifestation in 54 (41 females, 13 males) out of the 225 patients included (167 females, 58 males), with a prevalence of 24%. Main characteristics of arthritis and overal results has been completely reported in table 1 . Conclusions: We confirmed that an isolated polyarthritis is the first symptom of anti Jo-1 positive ASSD in up to a quarter of cases. Arthritis is mainly polyarticular and symmetrical, and the positivity for IgM RF or ACPA or both is not a rare finding, as well as the occurrence of marginal X-rays joint erosions. Anti-Ro positivity and RP occurrence may help clinician in the early identification of ASSD, even if the high rate of subsequent appearance of ILD and myositis clearly suggest that the screening for an underlying ASSD should be performed also in patients that may be undoubtedly diagnosed with RA. References: Cavagna L, et al. Characterization of anti Jo-1 positive antisynthetase syndrome: results from an international multicentre study. Arthritis Rheum 2014;11:S550. Lefèvre G, et al. Seronegative polyarthritis revealing antisynthetase syndrome: a multicentre study of 40 patients. Rheumatology (Oxford). 2014 Oct 27. pii:keu404. [Epub ahead of print] Disclosure of Interest: None declared